Persepsi Remaja terhadap Jumlah Anak Ideal di Kelurahan Ujung Batu Kecamatan Ujung Batu Kabupaten Rokan Hulu Provinsi Riau - Yulia Aini Dilla Rahayu; paus iskarni (JURUSAN GEOGRAFI FIS UNP, 2019)
This study aims to describe the perceptions of adolescents on the ideal number of children and find out the effect of education level, income level, and family size on the perception of adolescents about the ideal number of children in Ujung Batu Village, Ujung Batu District, Rokan Hulu District, Riau Province. This type of research is quantitative with cross-sectional method. The population in this study were adolescents who were in Ujung Batu Village. Samples were taken by convenience sampling method with a total of 96 adolescents. The results of the study found that the ideal number of children according to adolescents was 2 because it was based on government programs. The results of Chi Square analysis show that the condition of the level of education, the level of income of the head of the family and the size of the family have a significant influence on the number of ideal children.